Letter to Kathleen O'Brennan from Whitford Kane about Kathleen O'Brennan's play "Napper Tandy", and about family and acquaintances - Kane, Whitford, 1882-1956; O'Brennan, Kathleen M., 1876-1948 (1948)
Whitford Kane suggests changes, sent under separate cover, that Kathleen O'Brennan could make to her play as she "asked for my impressions".
Letter inscribed on headed paper "Whitford Kane / 325 West 14th Street / New York 14, N.Y." and "1238 North Orange Drive / Hollywood 38, Calif".
Keywords: O'Brennan, Kathleen M., -- 1876-1948 -- Correspondence; Kane, Whitford, -- 1882-1956; Mac Liammóir, Micheál, -- 1899-1978.; Edwards, Hilton, -- 1903-1982; Allgood, Sara, -- 1883-1950; Dublin Gate Theatre; Theater; United States -- History -- 1945-; Ireland -- History -- 1922-